Reproductive parameters of buffaloes subjected to pharmacological control of the estrous cycle: lowest cost x best benefit - Madrigal-Valverde, M.; Cavalcante, A.K.S.; Brito, L.S.; Vasconcelos, I.C.; Maggitti Junior, L.D.P.; Carôso, B.S.S.; Bittencourt, R.F.; Loiola, M.V.G.; Ribeiro Filho, A.L. (Polish Journal of Veterinary Sciences, 2026)
This study aimed to evaluate the effects of equine chorionic gonadotropin (eCG), Estradiol benzoate (EB) and Gonadotropin-releasing hormone (GnRH) on follicular dynamics and luteal characteristics of buffaloes (Bubalus bubalis). The animals were separated into four experimental groups: EB (n=10), EB+eCG (n=10), GnRH (n=10) and GnRH+eCG (n=10). Using B-mode and Power-Doppler ultrasound, follicular characteristics of the largest follicle, from day 9 until day 11, diameter of the preovulatory follicle, follicular area, total wall area of the preovulatory follicle, growth rate of the ovulatory follicle, vascularization in the wall area of the preovulatory follicle, percentage of vascularization in the wall area of the preovulatory follicle and moment of ovulation, were evaluated for follicular dynamics. Furthermore, on day 18 of the protocol, diameter of the corpus luteum, total area of the corpus luteum, vascularization of the corpus luteum, percentage of vascularization of the corpus luteum and the serum progesterone levels were also evaluated. Statistical analyses were performed using Tukey’s test, Kruskal-Wallis and repeated measures ANOVA with a 5% significance level. Statistically significant differences were found for diameter of the corpus luteum with 1.78±0.12cm in the EB+eCG group and 1.62±0.11cm in the EB group (p=0.047), as well as in the Progesterone dosages between the treatments GnRH+eCG (4.09±0.94ng/mL) and GnRH (2.80±0.70ng/mL), p=0.017. Regarding the variables assessed by Power Doppler, no statistical differences were found between the experimental groups. Finally, the price analysis revealed that the EB+eCG protocol is 19% cheaper than the GnRH+eCG protocol. Therefore, EB offers better cost/benefit on the reproductive parameters of buffaloes subjected to pharmacological control of the estrous cycle.